Integrated system for defining the best athletes and teams in arm wrestling in conditions of modern challenges - I.N. Nikulin (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and substantiate an integrated system for determining the rating of the best athletes and teams in armwrestling. Methods and structure of the study. The analysis of the data of scientific literary sources, protocols of competitions, expert evaluation was carried out. The protocol data of 19 official All-Russian arm wrestling competitions in 2022 were processed. The presidents of the regional armwrestling federations, members of the Presidium of the Russian Armwrestling Federation, leading coaches and judges (35 people) acted as experts. Results and conclusions. An integrated system for determining the best athletes and teams in armwrestling has been developed in the context of limited international competitions. The rating is compiled on the basis of taking into account the results of all official all-Russian competitions of the subject’s combined team and individual athletes in various tournaments over a certain period of time (classification period) - a calendar year. Criteria for determining the rating of the best teams of the constituent entities of the Russian Federation during the competitive season have been developed, providing for the ranking of official all-Russian competitions in a hierarchy into four levels of significance, taking into account three age groups: cadets, juniors and adults.